145PRole of Glasgow prognostic score in chemo-naïve patients with advanced biliary tract cancer and good performance status. (24th November 2019) - Moriwaki, T; Hasegawa, N; Yamamoto, Y; Yamada, T; Kanai, M; Kobayashi, S; Eguchi, H; Seo, S; Taketomi, A; Yoshimura, K; Hatano, E; Nagano, H; et al.
Abstract: Background: Glasgow prognostic score (GPS), which is defined with serum levels of two parameters, albumin >3.5 g/dl and C-reactive protein <1.0 mg/dl (both as 0, either as 1, and neither as 2), has a prognostic significance in various malignant solid tumors. In a small-scale retrospective study, GPS was useful as a prognostic factor for chemo-naïve advanced biliary tract cancer (ABTC) patients with good performance status (PS; defined with ECOG PS 0 and 1). We evaluated whether GPS was useful in large-scale prospective study for ABTC patients with good PS. Methods: ABTC patients with PS 0/1 and not missing laboratory data among the patients who received gemcitabine + cisplatin (GC) or GC + S-1 (GCS) in a phase III study (MITSUBA) were analyzed for factors with P < 0.2, using multivariate Cox proportional hazards model for overall survival (OS). In the exploratory analysis, OS was compared between GC and GCS according to GPS. Results: Clinical data were collected from 230 patients (113 patients in the GC arm and 117 patients in the GCS arm) among 241 patients. The proportion of patients was 43% in GPS 0, 35% in GPS 1, and 22% in GPS 2, respectively. In the univariate and multivariate analyses, GPS was an independent prognostic factor (hazard ratio [HR], 0.68; 95% confidence interval [CI], 0.56-0.81; P < 0.001). The median OS was 18.0 months (95%CI, 15.3-20.7), 12.6 months (95%CI, 11.4-13.8), and 7.2 (95%CI, 4.4-10.0) for patients with GPS 0, GPS 1, and GPS 2, respectively. The HRs of GCS to GC were 1.00 (95%CI, 0.64-1.55; P = 0.99), 0.72 (95%CI, 0.45-1.15; P = 0.17), and 0.57 (95%CI, 0.32-1.04; P = 0.07), for patients with GPS 0, GPS 1, and GPS 2, respectively. Conclusions: GPS was useful for chemo-naïve ABTC patients with good PS, and GCS might improve OS, especially in patients with poor prognosis. Legal entity responsible for the study: Kansai Hepato-Biliary Oncology Group. Funding: Taiho Pharmaceutical. Disclosure: T. Moriwaki: Speaker Bureau / Expert testimony: Taiho Pharmaceutical; Speaker Bureau / Expert testimony: Lilly. Y. Yamamoto: Speaker Bureau / Expert testimony: Taiho. T. Yamada: Advisory / Consultancy: Taiho; Speaker Bureau / Expert testimony: Lilly. A. Taketomi: Honoraria (institution), Leadership role: Taiho. K. Yoshimura: Honoraria (self): Taiho; Honoraria (self): Lilly; Honoraria (self): Nippon Kayaku. E. Hatano: Honoraria (self): Taiho; Honoraria (self), Advisory / Consultancy: Lilly. T. Ioka: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Taiho. All other authors have declared no conflicts of interest.